Coronal Spinal Balance in Adult Spine Deformity Patients With Long Spinal Fusions: A Minimum 2- to 5-Year Follow-up Study. Issue 9 (November 2015) - Ploumis, Avraam; Simpson, Andrew K.; Cha, Thomas D.; Herzog, Joshua P.; Wood, Kirkham B.
Abstract : Study Design: This study was a retrospective one. Objective: The objective of the study was to analyze the causes, prevalence of, and risk factors for coronal decompensation in long adult lumbar spinal instrumentation and fusion (from thoracic or upper lumbar spine) to L5 or S1. Summary of Background Data: Coronal and sagittal decompensation after long fusions for spinal deformities can affect outcomes negatively. There is no study reporting the natural history of coronal spinal balance after long spinal fusions. Methods: A single-center retrospective review of data from 54 patients with spinal deformity was performed. Inclusion criteria were patients over 18 years with long fusions (>4 segments) to L5 or the pelvis who had full spine standing radiographs before surgery and up to 2–5 years postoperatively. Radiographic data included C7PL, magnitude of scoliotic curve, shoulder or pelvic asymmetry in the coronal plane, thoracic kyphosis, lumbar lordosis, and pelvic parameters (pelvic incidence, pelvic tilt, sacral slope). Coronal imbalance (CI) was considered if the C7PL was >4 cm lateral to the central sacral line, and sagittal imbalance (SI) was considered when the C7 plumbline was >4 cm anterior to the middle of the upper sacral plate. Paired t test, χ 2 test, and repeated measures regression analysis using demographic data (age, sex, body mass index), operative (previous fusion, posterior only or anteroposterior fusion, iliac fixation or not, decompression or not, osteotomy or not) and postoperative (complications, use of bracing) data, and radiographic parameters (including SI) were performed. Results: Patients showing CI equaled 11 (19.3%) preoperatively, remained 11 (19.3%) (4 of whom were new patients with CI) at 6 weeks postoperatively, and increased ( P <0.001) to 18 (31.6%) (8 of them without initial CI) at 2–5 years follow-up. However, in terms of numeric distance of C7PL from the midsacrum, there was no statistically significant change ( P >0.05) from preoperative to last follow-up. SI showed significant improvement ( P <0.05) from preoperative to 6 weeks postoperative and no statistical significant change ( P >0.05) from 6 weeks to 2–5 years postoperatively. Repeated measures regression analysis showed that the presence of osteoporosis and the combination of anterior approach surgery with a history of previous surgery were significant ( P <0.05) factors predictive of changes in coronal balance. Conclusions: After surgical correction of spinal deformities, coronal spinal decompensation appears in an increased number of patients at last follow-up postoperatively but without significant differences in coronal plane C7PL during the postoperative period. Attention should be paid to patients with osteoporosis and those with a combination of previous same site posterior spine surgery and new anterior approach surgery for changes of coronal balance postoperatively.